Exploring novel algorithms for an improved ERT monitoring workflow - Hawley-Sibbett, Luke Richard (2023)
Electrical Resistivity Tomography (ERT) is a technique for estimating the resistivity of the subsurface. Long term ERT monitoring is increasingly used to estimate changes in resistivity over time, but data processing workflows are not fully developed. In this thesis, new methods are explored to improve important elements of the workflow: the regularisation of time-lapse inversions, and the detection of data quality anomalies which can be missed by conventional methods.